Amaurosis Fugax Preceeding Central Retinal Artery Occlusion : a Case Report - Ade John Nursalim; Vera Sumual; Andrew Cietra; Elbetty Simanjuntak; Christian Maramis; Komaling Komaling; Stevanus Josafat Loho (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
Amaurosis fugax is a temporary condition characterized by transient visual loss which lasts several minutes or hours. This symptom can precede central retinal artery occlusion, which can cause permanent visual loss and bear several morbidity and mortality risks. We are reporting a case of a 59-year-old female with an unknown history related to risk factors who developed a painless vision loss in her right eye after experiencing similar symptoms for a short time. We describe the clinical features and other findings related to the diagnosis and discuss the further risk and management. Medical history, physical examination, and optical coherence tomography diagnosed acute central retinal artery occlusion. This includes a history of painless monocular vision loss, macular cherry-red spots, and papilledema. The diagnosis was confirmed by optical coherence tomography showing hyperreflectivity in the inner retinal layer, retinal edema, and hyperreflectivity in the outer retinal layer. Blood test including complete blood check, erythrocyte sedimentation rate (ESR), C reactive protein, lipid profile, and inflammatory markers within normal limit. The patient was then administered to further secondary vascular occlusion prevention, including a blood test, and referred to the neurology department for further examination. Early diagnosis and prompt treatment are necessary for this occlusive disease. A comprehensive examination to mitigate secondary vascular occlusion is needed to prevent morbidity and mortality.